3D-printed aberration-free terahertz metalens for ultra-broadband achromatic super-resolution wide-angle imaging with high numerical aperture - Jin Chen; Shao-Xin Huang; Ka Fai Chan; Geng-Bo Wu; Chi Hou Chan (Nature Communications)
Abstract Terahertz (THz) lens constitutes a vital component in the THz system. Metasurfaces-based THz metalenses and classical bulky lenses are severely constrained by chromatic/ spherical aberration and the diffraction limit. Consequently, achromatic super-resolution THz lenses are urgently needed. In this study, through translating the required phase distribution into a refractive index (RI) profile with a specific thickness, an innovative approach to designing THz metalenses is proposed and achieved by dielectric gradient metamaterials. The samples fabricated by 3D printing can realize achromatic super focusing with a numerical aperture (NA) of 0.555 from 0.2 to 0.9 THz. Submillimeter features separated by approximately 0.2 mm can be resolved with high precision, such as glass fabric patterns within FR4 panels and fibrous tissue on leaves, with a field of view (FOV) of 90°. Our approach offers a feasible and cost-effective means to implement THz super-resolution imaging, which holds great potential in non-destructive testing and biomedical imaging.